Fixin internal fixator: Concept and technique - Petazzoni, M.; Urizzi, A.; Verdonck, B.; Jaeger, G. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
This report describes the Fixin internal fixator systema, a fracture fixation device characterised by a locking conical coupling between screw heads and titanium alloy inserts that are screwed into a stainless steel plate construct. The mechanical principles, implants, instruments and surgical technique are discussed.
Keywords: Internal fixator; osteosynthesis; locking plates; angle-stable plates; conical coupling